Study on water hammer effect on defective tubing failure in high pressure deep gas well. (December 2019) - Mou, Yisheng; Lian, Zhanghua; Sang, Pengfei; Yu, Hao; Zhang, Qiang; Li, Ran
Abstract: Tubing is a primary barrier to wellbore integrity and an important guarantee for normal production. However, tubing defect due to hydraulic tong can cause tubing deformation, strength degradation and even well abandonment under ultimate load due to water hammer effect caused by well closure. Hence, the experimental study on fractured surface of tubing is carried out to analyze fracture characteristics. On the other hand, the finite elements model (FEM) of water hammer effect is established to calculate pressure variation in tubing. Finally, the FEM of the defective tubing caused by hydraulic tong is established to analyze stress distribution of tubing with indentations under the load caused by water hammer effect, annulus protection fluid and axial force. The results show that the water hammer effect can be caused by closure of the HP deep wells in tubing instantly, the maximum pressure reaches 116 MPa in X-well, and the severe stress concentration (895.29 MPa) at the rounded corners of each indentations can be caused. The characteristics of ductile fracture on fractured surface is pretty obvious according to experimental researches and FEM analysis. The researches presented in this paper can provide reference and guidance for preventing tubing and reduce economic losses. Highlights: A three-dimensional finite element model of defective tubing is established. The experimental study on fractured surface of tubing is carried out to analyze fracture characteristics. The finite elements model (FEM) of water hammer effect is established to calculate pressure variation in tubing. Stress concentration is analyzed under the load caused by water hammer effect, annulus protection fluid.